CARDIORRHEXIS: REPORT OF ONE SUCCESSFUL CASE (Vietnam Journal of Community Medicine, 2022)
Report a rare case of cardiorrhexis: A 14month-old patient with a cardiorrhexis wassuccesfully operated at Nghe An Obstetrics andPediatrics Hospital. The surgery is supported bythe external circulation extracoporelle.Cardiorrhexis in children is a rare injury. Thediagnosis and treatment of cardiorrhexis isdifficult. However, the patient can still betimely rescued.
Keywords: Cardiorrhexis *Corressponding author: Tang Xuan Hai Email address: bstangxuanhai@gmail.com Phone number: 0912379583 http://doi VỠ TIM: BÁO CÁO TRƯỜNG HỢP ĐIỀU TRỊ THÀNH CÔNG Tăng Xuân Hải, Lê Trọng Thông, Trần Minh Long, Trần Văn Trung, Nguyễn Hữu Việt Bách 1Sở Y tế Nghệ An 2Bệnh viện Sản Nhi Nghệ An Ngày nhận bài: Chỉnh sửa ngày:; Ngày duyệt đăng: TÓM TẮT Một bệnh nhân 14 tháng tuổi bị vỡ tim đã được phẫu thuật cấp cứu thành công, có sự hỗ trợ của hệ thống tuần hoàn ngoài cơ thể tại Bệnh viện Sản Nhi Nghệ An. Vỡ tim trẻ em là một chấn thương hiếm gặp, chẩn đoán và điều trị vỡ tim khó khăn nhưng vẫn có thể cứu sống người bệnh kịp thời. Từ khóa: Chấn thương t